The Right of Habitation over Property Co-owned by a Non-custodial Parent and a Third Party (Family Act, Article 194) – Part One – - Midorović, Sloboda D; Cvetić, Radenka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This paper examines whether, in light of the wording of Article 194 of the Family Act (FA) and Articles 14–16 of the Law on the Fundamentals of Property Relations (LFPR), a court may establish a right of habitation over immovable property co-owned by a parent and a third party. While domestic case law tends to accept such a possibility, arguing that it is "not excluded by the Family Act," the authors contend that this approach, on the one hand, reads into the FA something it does not provide—namely, that the (co-)ownership of a person who is not the parent may be burdened by a right of habitation—and, on the other hand, disregards the rights attached to co-ownership under the LFPR. As a result, the co-owner who is not the parent is effectively deprived—until the child reaches majority—of all entitlements that the LFPR associates with a co-owner´s status. In particular, the non-parent co-owner is thus stripped of his/her entitlements to possess, use (including the right to collect civil fruits), dispose of, and participate in the management of the co-owned property, as well as, the ability to request partition of the co-ownership at any time, except during inconvenient circumstances. In doing so, the domestic judicature, guided by considerations of fairness and the "best interests of the child", effectively abrogates part of the applicable legislature. The paper first outlines the general regime of the personal servitude of habitation. It then analyses the legal structure of the habitatio in light of Article 194 FA and its relation to the right to the protection of a home under the case law of the European Court of Human Rights, with which it is often erroneously conflated. The paper further discusses the general rules on co-ownership under the LFPR, placing particular emphasis on how a right of habitation may be established over co-owned property. The analysis of domestic case law, solutions that would remain within the boundaries of the FA and the LFPR, as well as the conclusion on whether legislative intervention is necessary and desirable, will be presented in the second part of the paper.
Keywords: right of habitation, child, co-ownership, right to respect for a child’s home, court decision.